DESKRIPSI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL-SOAL PERUBAHAN WUJUD ZAT DI KELAS VII SMP KEMALA BHAYANGKARI - Rianti, Rianti; Harun, A. Ifriany; Melati, Husna Amalya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study was to describe the error form students grade of VII SMP Kemala Bhayangkari on material changes. The research method was descriptive. The subjects of this study were students grade of VII A SMP Kemala Bhayangkari. As well as twenty two students were used as subject in this research. Data collection tools are a cause-and-effect test and interview guide. The result show that the average error in understanding the essential concepts, the errors in understanding the relationship between concepts, and the errors in understanding the use of concepts to solve problems are 38%, 28%, and 25% respectively. The student is wrong in understanding the concept of change of being, unable to determine the physical and chemical properties, physical changes and chemical changes, and the characteristics of chemical reactions. Students are wrong in understanding the relationship between the concept of temperature and phase change, the characteristics of objects with physical properties and chemical properties, color changes with chemical reactions, solubility with ionization power. Students are wrong in analyzing the physical and chemical properties of an event, analyzing the physical changes and chemical changes in an event. Errors that students do due to less of attention during the learning process, less of note complete, less of material understanding and less of order in the classroom.Keyword: Form of Error, Substance Changes